DEVELOPMENT OF LISTENERS’ DIGITAL COMPETENCE AS A SCIENTIFIC PROBLEM IN THE PROCESS OF TRAINING - Baxshillo Amrilloyevich Olimov (Galaxy International Interdisciplinary Research Journal, 2023)
In the article modern educational digital technologies opportunities , them qualification increase of the audience how it affects the learning process and issues related to the main problems in the development of the digital competence of the listeners were studied .